ANALYSIS OF E-CLEARANCE CARE (SIERA) APPLICATION USING THE USABILITY TESTING METHOD AT CLASS I IMMIGRATION OFFICE TPI TANJUNG PERAK - W Wilonotomo; P. Assiroj; A.A Wibowo (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2022)
Tanjung Perak Immigration Office, in the development of digitalization, launched an innovation called E-Clearance Care (SIERA) which aims to simplify the service process, especially at sea immigration checkpoints. E-Clearance care is an information system to support the licensing process and collect information on the passage of people entering or leaving Indonesian territory from vehicles along with those in charge and crew of transportation equipment. Through the e-clearance application, notifications of ship arrival or departure can be submitted electronically, it can reduce inspection time at immigration checkpoints. This research was conducted to analyze e-clearance care applications using indicators of usability, namely learnability, efficiency, memorability, error, and satisfaction. The results of the assessment of this application for each usability variable still need additions to the notification menu to make it easier for officers to monitor each arrival or departure of ships. Apart from that there is a need for improvements to the display menu to make it more attractive and increase network speed in the building where immigration checks are to minimize disturbance.